1998
DOI: 10.1094/cchem.1998.75.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of U.S. Wheats Carrying Null Alleles at the wx Loci

Abstract: Cereal Chem. 75(1):162-165Granule-bound starch synthase (GBSS) is the primary enzyme responsible for the synthesis of amylose in amyloplasts of cereal endosperm cells. Bread wheats, due to their hexaploid genetic system, carry three genes (wx loci) encoding GBSS. Purification and separation of GBSS from more than 200 North American hexaploid wheats allowed the identification of genotypes that carry null alleles at either the wx-A1 and wx-B1 loci. In addition, the cultivar Ike carried both wx-A1 and wx-B1 null … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 11 publications
(19 reference statements)
0
47
0
Order By: Relevance
“…This might be due to the contribution of enzyme from vetch flour. Generally, in leavened dough, too much amylase activity can cause wet, sticky crumb with large voids in the loaf and too little can cause dry, crumbly crumb and high loaf density but in this case, too much amylase did not observe that could cause any deleterious effect on the doughnuts at all levels of vetch substitution (Graybosch et al, 1998;Graybosch, Guo, & Shelton, 2000).…”
Section: Fn Of Composite Floursmentioning
confidence: 84%
“…This might be due to the contribution of enzyme from vetch flour. Generally, in leavened dough, too much amylase activity can cause wet, sticky crumb with large voids in the loaf and too little can cause dry, crumbly crumb and high loaf density but in this case, too much amylase did not observe that could cause any deleterious effect on the doughnuts at all levels of vetch substitution (Graybosch et al, 1998;Graybosch, Guo, & Shelton, 2000).…”
Section: Fn Of Composite Floursmentioning
confidence: 84%
“…Other authors also found these null variants in materials from all over the world (Graybosch et al 1998;Rodriguez-Quijano et al 1998;Urbano et al 2002). The null Wx-D1 allele is, however, extremely rare and has only been described in few cultivars (Yamamori et al 1994;Urbano et al 2002;Guzman et al 2010).…”
Section: Introductionmentioning
confidence: 89%
“…With the availability of waxy wheat, it is possible to manipulate tlour amylose content without dilution of wheat gluten (Graybosch 1998;Grayboseh et al 1998). Up to now, therc has been only one report of the impact of amylose content on wheat tortilla processing and product quality (Waniska et al 2(X)2), and pm1ial waxy wheats with slightly (\.0-3.3%) lower amylose content were used in that study.…”
mentioning
confidence: 99%